Relationships between bone age, physical performance, and motor coordination among adolescent male and female athletes - Hilde Gundersen; Knut Marius Navelsaker Kvammen; Mona Vestbøstad; Cecilie Brekke Rygh; Cecilie Brekke Rygh; Halvard Grendstad (Frontiers in Sports and Active Living)
Biological maturity significantly impacts youth athletes’ physical performance throughout adolescence. However, how this differs between male and female youth athletes remains unclear. Thus, the present study aimed to assess associations between maturity, physical performance and motor coordination in females and males. Sixty-eight youth athletes (mean age 13.9 ± 0.8 years, 26 females) were included in the present study. Participants performed a 40 m sprint, standing long jump (SLJ), push-ups and a 2,000 m run. Motor coordination was evaluated using the short form of the Körperkoordinationstest für Kinder test. Bone age (BA), assessed by x-ray of the left hand and analyzed with an automated software, was used as a biomarker of biological maturity. Results showed that BA was significantly associated with performance for males on 40 m sprint (r = −.556, p < .001), SLJ (r = .500, p < .001) and 2,000 m run (r = −.435, p = .011). No associations were found between BA and physical performance among females, nor between BA and motor coordination for either females or males. In conclusion, maturity is associated with exercises that require maximal speed, explosive leg strength and endurance in males, but not in females, with maturity showing no impact on the motor coordination in either sex.